Information Technology-Based Efforts to Handle Stunting Problems in Sriwedari Village - Maimunah, M; Purnomo, Tito Rizki; Basunondro, Wibiartono; Fadhilah, Alfira Nisa; Safitri, Renjani Lulu; Bilqis, Lauda Khansa (Universitas Muhammadiyah Surakarta, 2023)
This integrated community service activity was carried out to address the problem of stunting in Sriwedari Village, Salaman District, Magelang Regency. Handling problems regarding stunting includes two aspects: the economic aspect and monitoring the development of stunting toddlers. The unavailability of a stunting monitoring system has resulted in not being monitored for child growth and development. Several factors, including the economy cause the high stunting rate. In this community service activity, assistance is carried out for MSME Dried Potatoes Ms. Dwi based on digital marketing and creating a stunting monitoring information system. Efforts to solve these problems are expected to help the problem of stunting in Sriwedari Village.